2021
DOI: 10.1111/afe.12477
|View full text |Cite
|
Sign up to set email alerts
|

Ant (Hymenoptera: Formicidae) ‐ aphid (Hemiptera: Aphididae) interactions in different habitats from Turkey with new mutualistic associations

Abstract: This study aimed to investigate the interactions between ants and aphids on host plants in different habitats located in the northwestern part of Turkey. A total of 26 ant species belonging to 13 genera and 3 subfamilies from the family Formicidae (Hymenoptera) were found associated with 52 aphid species belonging to 22 genera from the family Aphididae (Hemiptera: Aphidoidea) on 66 host plant species from 24 plant families. In total, 132 tritrophic ants–aphids–host plants interactions including new association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In support of this, a study including the results on the interactions of ant-aphids and aphid-host plants in different habitats by Kök et al . (2022) revealed that the specialization of ants and aphids in the uncultivated areas was higher than in cultivated and urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, a study including the results on the interactions of ant-aphids and aphid-host plants in different habitats by Kök et al . (2022) revealed that the specialization of ants and aphids in the uncultivated areas was higher than in cultivated and urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, it is notable that the detection of the most common species (A. robiniae with 360 specimens) on the host plant R. pseudoacacia, was from only two sampling areas using systematic sampling. It is concluded that A. robiniae was among the highest detected species as a result of its host plant-specific nature (Görür et al, 2014(Görür et al, , 2020Oğuzoğlu & Avcı, 2019;Kök et al, 2020Kök et al, , 2022Kök & Özdemir, 2021;Patlar et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…There are different selective pressures in urban habitats acting on ants and aphids, which may influence their mutualistic interaction. Recent studies reported an effect of urbanisation on the intensity (Kremer et al., 2018 ), diversity (Kök et al., 2022 ) and outcome (Rocha & Fellowes, 2020 ) of ant‐aphid mutualisms. The potential changes in ant and aphid traits and behaviour remain largely unknown, however.…”
Section: Introductionmentioning
confidence: 99%